116 Substance use in non-transport injury events: A systematic review and meta-analysis. (20th November 2022) - Lau, Georgina; Ang, Jia; Kim, Nayoung; Gabbe, Belinda; Mitra, Biswadev; Dietze, Paul; Reeder, Sandra; Beck, Ben
Abstract : Background: Substance use is a key preventable risk factor for injury. However, current prevention efforts largely focus on substance use in road transport injury, with other injury causes receiving less attention. This review aims to summarise research on the prevalence of substance use in non-transport injuries. Methods: Observational studies published in English after 2009 were identified by searching electronic databases, grey literature and reference lists. Eligible studies (1) examined individuals ≥15 years presenting to a hospital or forensic centre following a non-transport related injury; and (2) included an objective toxicology measure. Meta-analyses were performed where appropriate. Results: Two reviewers independently screened 11, 413 records and 2, 078 full-text articles. Of these, 122 studies were included. Most studies reported on alcohol (n=114, 93%) with varying prevalence (falls: 4–57%, assaults: 10–71%, firearms: 21–42%, penetrating injuries: 9–25%, suicides: 20–50%). Less research examined other drugs including cannabis (n=18), amphetamines (n=14), cocaine (n=14), opioids (n=10) and benzodiazepines (n=7). In meta-analyses, 37% of fall-related injuries involved any substance use, 35% of firearm injuries involved alcohol and 31% of suicides involved alcohol. Conclusion: Substance use is prevalent across injury causes. However, prevalence varied between studies and inadequate reporting of study methods often impaired comparison of these results. Learning Outcomes: Given the prevalence of substance use in non-transport injuries, there is need for targeted injury prevention and harm minimisation strategies addressing these injury causes. Future research should focus on the role of drugs other than alcohol in specific injury causes and would benefit from improved reporting of toxicology testing methods.